Mulheres na Política e Autonomia - Rabay, Glória de Lourdes Freire (2008)
The proposal of this study was to work with women in the politics, focusing on their trajectories, biographies and speeches, to catch the meanings given by themselves to their insertion in the political field. The privileged instrument of research was the autobiographical narratives of fifteen women who, in Paraíba, had participated of the electoral processes and the life partisan politics in the period from 1998 to 2008, in the state and federal scopes. This permitted us to search the dimension of their lived expericence, to understand the trajectories and the processes of autonomation of the women, in the politics. Moreover, a quantitative mapping of the feminine presence in the processes was made electoral politicians in a wider context. In a similar way, two surveys had been carried throughout the research, among others aspects, to understand that image voters and politicians they construct concerning the feminine participation in this field. These instruments were important not to lose of all the social view where these lives were developed, the places from which these women speak and locate and the social meanings originated from this participation. The research aimed to establish dialogues between knowing and fields of discipline, beyond the dichotomy of actor/structure, preventing generalizations that ignore the plurality of the individuals, to reveal some aspects of the complex and contradictory processes that involve their participation in the political field. At last, it is tried to show that, although the frequent accusations of autonomy lack, when establishing relations in the public space, the women, as all subjects, can reflect about themselves, the motives of their thoughts and their actions escaping from the servitude of the repetition and avoid being only product of the institution that formed them (CASTORIADIS, 1992, p.140-141)